Cognitive principles of the Andean culture - Meneses Tutaya, Norma (2018)
The results of an investigation carried out to determine the cognitive principles of the Andean people are presented here. The research was based on an approach to the daily discourse, especially anecdotes, of some collaborators who recognize themselves from andean origins. It is shown that these principles are not exclusive to the Andean culture and the only thing particular to it is the hierarchy they present. The ten most important cognitive principles are animism-dynamism, helical circularity of time, duality, diversity-variation, systematic-functionality, similarity, continuum-totality, practicality, prospectivity.